An Ecocriticism on Anthropocentrism in Dune (2021) - Ilham Novendra; Fitra Mandela; Novi Dwi Gitawati (Asosiasi Dosen Muda Indonesia, 2026)
This research aims to find the impact of human activity and interaction with their surrounding nature as well as to illustrate how anthropocentrism is portrayed in the Dune movie. This research applied descriptive qualitative method, while the data collected by observing the scene and dialogue that contains ecocriticism and anthropocentrism in the movie Dune. This research applies the theory of Greg Garrard and Cheryll Glotfelty for ecocriticism. This research also applies the theory of Bryan Norton for anthropocentrism types and its impact. Based on the result of selected data, the types of anthropocentrism depicted in the movie are 12 strong anthropocentrism and 5 weak anthropocentrism. As for the impact of anthropocentrism found in the movie are 5 anthropocentrism impact. All of the anthropocentrism types depicted in the movie are basically an implementation of human thought which considers human to be the center of the universe and justifies all action to achieve what one’s desired. Based on the data, strong anthropocentrism tends to exploit nature, dominate nature, and oppress other living creature for human interest. Weak anthropocentrism tends to preserve nature due to human’s dependency with nature. Anthropocentrism caused the impact on environment and living creature including human.